2015
DOI: 10.3855/jidc.5255
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine levels are associated with the severity of varicella infections

Abstract: Introduction: Varicella is a highly contagious disease. Epidemics of varicella are seen every year globally and present a threat to public health, especially in China and other developing countries. Methodology: Clinical and laboratory findings of 865 varicella patients admitted to Beijing You'an Hospital, China, between January 2011 and December 2013 were collected and analyzed. Patients with isolated complication were grouped as SI (skin infection, n = 132) and LD (liver damage, n = 89). Two hundred and one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…It is known that dominant role in controlling dissemination and generalization of varicella zoster virus belongs to the cellular immunity of Th1-type [8,16,17]. Recently, special attention has been paid to study the role of IL-10 in the course of this infection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is known that dominant role in controlling dissemination and generalization of varicella zoster virus belongs to the cellular immunity of Th1-type [8,16,17]. Recently, special attention has been paid to study the role of IL-10 in the course of this infection.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with a moderate course of herpes zoster, the authors [7,21] found an increase in blood levels of IL-10, which was treated as an adequate immunological response to the virus, with ability to reconvalescence without development of different complications. However, in severe course of shingles there was an insufficient immunological reactivity of the organism, which was characterized by a constant level of IL-10 [8,17]. All of this scientific researches has a definite pathogenetic explanation, namely it is known that in damage of brain cells, neurogliocytes produce IL-10, which increases the vitality of brain cells [16,25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, IL-6 and IFN-γ may be used as early serum markers for the development of complications of VZV disease such as skin infection [408]. VZV infection of primary spinal cord astrocytes causing myelopathy and VZV infection of primary hippocampal astrocytes that causes encephalopathy have produced distinctive alterations and patterns of proin lammatory cytokine suppression that could contribute to the ineffective viral clearance in both VZV associated myelopathy and encephalopathy [409].…”
Section: Role Of Cytokines In Vzv Infectionsmentioning
confidence: 99%